Dimensions of a healthy lifestyle among early adolescents: The simultaneous contribution of spirituality and family cohesiveness. - Mahensa, Iqnes Restual; Kinanthi, Melok Roro; Febriani, Zulfa (Indigenous, 2022)
Abstract. Early adolescents are prone to develop an unhealthy lifestyle. Along with personal factors, the microsystem’s environment can influence individual development. This study aims to examine whether a personal factor (spirituality) and a microsystem factor (family cohesiveness) simultaneously contribute significantly to a healthy lifestyle among early adolescents. A quantitative approach was applied in thisstudy, involving 166 participants in Jakarta, selected by convenience sampling. Health Promoting Lifestyle Profile II (Cronbach’s alpha = 0.800 - 0.840), the Brief Multidimensional Measure of Religiousness/ Spirituality (Cronbach’s alpha = 0.725), and the Brief Family Relationship Scale (BFRS) – cohesiveness dimension (Cronbach’s alpha = 0.934) were employed to collect data. Multiple regression analysis revealed that spirituality and family cohesiveness simultaneously contributed significantly to the healthy lifestyle of early adolescents, with a contribution of 6.1% to 30.9%. Thus, concurrently individual and family based approaches should be considered in designing interventions to promote a healthy lifestyle in early adolescents. Keywords:  healthy lifestyle; spirituality; family cohesiveness.